NOTCH Signaling in T-Cell-Mediated Anti-Tumor Immunity and T-Cell-Based Immunotherapies - Kelliher, Michelle A.; Roderick, Justine E. (Frontiers in Immunology, 2018)
The NOTCH (1–4) family of receptors are highly conserved and are critical in regulating many developmental processes and in the maintenance of tissue homeostasis. Our laboratory and numerous others have demonstrated that aberrant NOTCH signaling is oncogenic in several different cancer types. Conversely, there is also evidence that NOTCH can also function as a tumor suppressor. In addition to playing an essential role in tumor development, NOTCH receptors regulate T-cell development, maintenance, and activation. Recent studies have determined that NOTCH signaling is required for optimal T-cell-mediated anti-tumor immunity. Consequently, tumor cells and the tumor microenvironment have acquired mechanisms to suppress NOTCH signaling to evade T-cell-mediated killing. Tumor-mediated suppression of NOTCH signaling in T-cells can be overcome by systemic administration of NOTCH agonistic antibodies and ligands or proteasome inhibitors, resulting in sustained NOTCH signaling and T-cell activation. In addition, NOTCH receptors and ligands are being utilized to improve the generation and specificity of T-cells for adoptive transplant immunotherapies. In this review, we will summarize the role(s) of NOTCH signaling in T-cell anti-tumor immunity as well as TCR- and chimeric antigen receptor-based immunotherapies.